A systematic review of interventions by healthcare professionals on community-dwelling postmenopausal women with osteoporosis - Lai, P.; Chua, Siew Siang; Chan, S.P. (Springer, 2010)
A systematic review was conducted to evaluate evidence concerning the effect of non-drug interventions by healthcare professionals on community-dwelling postmenopausal osteoporotic women. Evidence available indicates that such interventions are effective in improving the quality of life, medication compliance, and calcium intake, but effect on other outcomes is less conclusive. The purpose of this study is to conduct a systematic review to evaluate evidence concerning the effect of non-drug interventions by healthcare professionals on community-dwelling postmenopausal osteoporotic women. Randomized controlled trials (RCTs) published in English between year 1990 and 2009 were identified. Types of patient outcome used as assessment included quality of life (QOL), bone mineral density (BMD), medication compliance and persistence, knowledge level, and lifestyle modification. Twenty four RCTs met the inclusion criteria. Seven studies assessed interventions by physiotherapists, six by physicians, seven by nurses, three by multi-disciplinary teams and one by dietitians. Variability in the types and intensity of interventions made comparison between each study difficult. Collectively, these studies provided some evidence to show that interventions by healthcare professionals improved the QOL medication compliance and calcium intake of patients but its effects on BMD, medication persistence, knowledge, and other lifestyle modifications were less conclusive. From this review, it was found that some outcome measures of such non-drug interventions still required further studies. Future studies should use validated instruments to assess the outcomes, with focus on common definitions of interventions and outcome measures, more intensive one-to-one interventions, appropriate control groups, adequate randomization procedures, and also provide information on effect size.